2002
DOI: 10.14776/kjpid.2002.9.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Pulmonary Paragonimiasis in a Family after Ingestion of Raw Fresh-water Crayfishes caught in a Stream of Wolchulmountain

Abstract: Human infection with the lung fluke Paragonimus westermani has become rare in Korea.Human paragonimiasis is caused by eating raw fresh-water crayfishes or crabs infected with larval metacercariae. Recently, we experienced three cases of pulmonary paragonimiasis in a family. They ate raw fresh-water crayfishes that lived in a stream in Wolchulmountain. All the parients had hypereosinophilia and pulmonary infiltrates with pleural effusion or hydropneumothorax, which did not improve on antibiotics. Ingestion of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This is consistent with a previous report23), showing a high prevalence of paragonimiasis in the Jollanam-do area, Moreover, the prevalence of paragonimiasis in urban areas has been reported to be on the increase, because of an increasing number of tourists, population mobility, and the spread of regional food cultures24). Although improvements in the hygienic environment and hygiene campaigns have reduced the overall parasitic infection rate, from 6.7% in 199723) to 2.4% in 1997, the incidence of paragonimiasis has not decreased, because of ingestion of raw fish and salted crab. Indeed, we found that eight patients diagnosed with paragonimiasis had eaten salted freshwater crabs or taken raw crayfish juice.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with a previous report23), showing a high prevalence of paragonimiasis in the Jollanam-do area, Moreover, the prevalence of paragonimiasis in urban areas has been reported to be on the increase, because of an increasing number of tourists, population mobility, and the spread of regional food cultures24). Although improvements in the hygienic environment and hygiene campaigns have reduced the overall parasitic infection rate, from 6.7% in 199723) to 2.4% in 1997, the incidence of paragonimiasis has not decreased, because of ingestion of raw fish and salted crab. Indeed, we found that eight patients diagnosed with paragonimiasis had eaten salted freshwater crabs or taken raw crayfish juice.…”
Section: Discussionsupporting
confidence: 94%